Facile modulation of optical properties of octagold clusters through the control of ligand-mediated interactions. Issue 28 (5th July 2016) - Iwasaki, Mitsuhiro; Kobayashi, Naoki; Shichibu, Yukatsu; Konishi, Katsuaki
Abstract : Organic ligand environments substantially affect the optical properties of gold clusters through electronic and steric interactions, offering versatile tools to tune cluster properties. Abstract : In the recent development of structurally defined ligand-stabilized gold clusters, it has been revealed that not only the inorganic units but also the surrounding organic ligands substantially affect their electronic/optical properties. In this work, a series of core + exo type Au8 clusters decorated by dppp (Ph2 P(CH2 )3 PPh2 ) and arylthiolate ligands ([Au8 (dppp)4 (SR)2 ] 2+, 1–5 ) were synthesized, and their optical properties were studied in order to gain insights into the perturbation effects of the organic ligands.1–5 showed visible absorption and photoluminescence emission bands at longer wavelengths compared to their chloro- and acetylide-modified analogues, suggesting the contribution of weak non-bonding interactions of the Au framework with the ligand heteroatoms. Upon acid treatment, 2- and 4-pyridinethiolate clusters (R = Py, 2 and4 ) showed larger red shifts of the absorption and emission bands than the 3-pyridyl isomer (3 ), implying the involvement of the resonance structures of the SPy units. On the other hand, all regioisomers (2–4 ) showed large photoluminescence enhancements upon pyridine protonation. X-ray crystallographic and NMR analyses of4 and its protonated form (4′ ) showed that the electron-deficient pyridinium rings of4′ form π-stacks with neighbouring phenyl groups of dppp, suggesting that the orientation of the surface aromatics is a plausible factor governing the emission efficiency. These observations provide examples of successful modulation of optical properties of small gold clusters through the electronic and/or steric perturbation by the proximal organic ligands, highlighting the importance of the ligand design in the fine tuning of cluster properties directed for optical chemosensors and luminescent materials.